2015
DOI: 10.1111/tpj.13076
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetyltransferase GCN5 is essential for heat stress‐responsive gene activation and thermotolerance in Arabidopsis

Abstract: SUMMARYExposure to temperatures exceeding the normal optimum levels, or heat stress (HS), constitutes an environmental disruption for plants, resulting in severe growth and development retardation. Here we show that loss of function of the Arabidopsis histone acetyltransferase GCN5 results in serious defects in terms of thermotolerance, and considerably impairs the transcriptional activation of HS-responsive genes. Notably, expression of several key regulators such as the HS transcription factors HSFA2 and HSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 72 publications
3
109
1
Order By: Relevance
“…C18:3, C16:3) content positively correlates with thermotolerance (Murakami et al ., ; Matsuda et al ., ; Roman et al ., ). Thus, the decreased ALA (C18:3) content in the gcn5 mutant leaves is inconsistent with our previous observation that the loss of GCN5 function results in significant defects in thermotolerance (Hu et al ., ), which indicates that GCN5‐mediated lipid metabolism and thermotolerance are relatively independent.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…C18:3, C16:3) content positively correlates with thermotolerance (Murakami et al ., ; Matsuda et al ., ; Roman et al ., ). Thus, the decreased ALA (C18:3) content in the gcn5 mutant leaves is inconsistent with our previous observation that the loss of GCN5 function results in significant defects in thermotolerance (Hu et al ., ), which indicates that GCN5‐mediated lipid metabolism and thermotolerance are relatively independent.…”
Section: Discussionmentioning
confidence: 96%
“…Histone acetylation/deacetylation is a dynamic process that plays an important role in gene regulation through the antagonist actions of HATs and HDACs. As a HAT, GCN5 is a versatile regulator of Arabidopsis biology, including floral meristem development, light responsiveness, root growth, thermotolerance and iron homeostasis (Bertrand et al ., ; Benhamed et al ., ; Kornet and Scheres, ; Hu et al ., ; Xing et al ., ). We observed that GCN5 is essential for lipid metabolism in Arabidopsis seeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCN5 is a versatile regulator of developmental and inducible gene expression in Arabidopsis and is required for the regulation of divergent sets of stress response genes (Servet et al ., ; Hu et al ., ; Xing et al ., ). To illustrate the mechanisms underlying the involvement of GCN5 in salt stress responses, we identified 1330 genes that were upregulated after salt stress, of which 471 are affected by GCN5.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Wang et al (2016) recently reported that Arabidopsis mutants in a number of histone deacetylases exhibit changes in seed fatty acid composition and that H3K9/14 acetylation of FAD3 influences its expression level (Wang et al, 2016). DNA acetylation in Arabidopsis has been implicated in heat stress-responsive gene expression (Hu et al, 2015). Therefore, although an hd2d mutant has yet to be analyzed, it is conceivable that this gene might play a role in controlling v-6 ΔDE.…”
Section: )mentioning
confidence: 99%